2002
DOI: 10.1104/pp.004226
|View full text |Cite
|
Sign up to set email alerts
|

Sterol C-24 Methyltransferase Type 1 Controls the Flux of Carbon into Sterol Biosynthesis in Tobacco Seed

Abstract: The first committed step in the conversion of cycloartenol into ⌬ 5 C24-alkyl sterols in plants is catalyzed by an S-adenosylmethionine-dependent sterol-C24-methyltransferase type 1 (SMT1). We report the consequences of overexpressing SMT1 in tobacco (Nicotiana tabacum), under control of either the constitutive carnation etched ring virus promoter or the seed-specific Brassica napus acyl-carrier protein promoter, on sterol biosynthesis in seed tissue. Overexpression of SMT1 with either promoter increased the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 26 publications
(49 reference statements)
6
59
0
Order By: Relevance
“…The presence of the alkyl group at C-24 that originates from this reaction is the structural characteristic differentiating C-24 alkylsterol from cholesterol. Therefore, cholesterol levels in plants are hypothesized to be modulated by SMT; this hypothesis is supported by the lower cholesterol level in transgenic plants that overexpress SMT and the higher cholesterol level in SMT knockout plants (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). However, the considerable amounts of cholesterol and its derivatives, SGAs, in solanaceous plants have suggested that these plants have a mechanism to produce cholesterol that is distinct from other plants.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of the alkyl group at C-24 that originates from this reaction is the structural characteristic differentiating C-24 alkylsterol from cholesterol. Therefore, cholesterol levels in plants are hypothesized to be modulated by SMT; this hypothesis is supported by the lower cholesterol level in transgenic plants that overexpress SMT and the higher cholesterol level in SMT knockout plants (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). However, the considerable amounts of cholesterol and its derivatives, SGAs, in solanaceous plants have suggested that these plants have a mechanism to produce cholesterol that is distinct from other plants.…”
Section: Discussionmentioning
confidence: 96%
“…In plants, cycloartenol is the first D 24(25) -sterol. If cycloartenol is reduced to cycloartanol by SSR2, the biosynthetic pathway would be efficiently redirected toward cholesterol (Figure 1) (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). We conducted in vitro assays to examine whether SSR2 has cycloartenol reductase activity and to compare the substrate specificities of SSR1 and SSR2 (Figure 4).…”
Section: In Vitro Enzymatic Activity Assays Of Ssrsmentioning
confidence: 99%
“…In all plants the critical slow step in phytosterol synthesis is associated with the C-methylation of cycloartenol [24][25][26]. In vascular plants and many fungi such as Pneumocystis carinii, the product of the SMT1 catalyzed reaction can be processed to be the substrate of SMT2 that controls the ratio of 24-methyl to 24-ethyl ∆ 5 -sterols.…”
Section: Smt Propertiesmentioning
confidence: 99%
“…For the upper systemic leaf 6, which corresponds to the position of the leaf assayed in Figure 7, 3 cpm of sterol per milligram of dry weight tissue was recovered from the petiole, which corresponds to 2.4 mg of obtusifoliol per gram of dry weight tissue. Considering that, in plants, obtusifoliol represents from 0.1% to 1% of the total sterol fraction and that total sterols sum up to 2,500 to 4,000 mg per gram of dry weight tissue (Schmitt and Benveniste, 1979;Schaeffer et al, 2001;Holmberg et al, 2002;Schrick et al, 2004), this indicates that a normal physiological concentration of obtusifoliol would be 2.5 to 40 mg per gram of dry weight tissue, suggesting that the observed levels of C14-labeled obtusifoliol detected in leaves 4 and 6 would be in the physiological range of obtusifoliol concentrations.…”
Section: Obtusifoliol Can Act As a Signaling Molecule And Moves Throumentioning
confidence: 99%
“…Overexpression, down-regulation, and mutant analyses of enzymes involved in sterol biosynthesis before the step leading to sitosterol and campesterol synthesis (SMT1, C24-methyltransferase; CYP51, C14-demethylase; FACKEL, C14-reductase; HYDRA1, D8-D7 sterol isomerase) influence the amount of campesterol and the balance between sitosterol and BRs (Schaller et al, 1998;Jang et al, 2000;Schrick et al, 2000;Kushiro et al, 2001;Sitbon and Jonsson, 2001;Holmberg et al, 2002;Souter et al, 2002). The smt1 mutant also shows a defect in vascular patterning (Carland et al, 2002), and smt1, fk, and hyd1/2 cannot be rescued by exogenous application of BRs.…”
mentioning
confidence: 99%